KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS THE UTILIZATION OF ORA-QUICK HIVST AMONG PREGNANT MOTHERS ATTENDING ANC AT ERRH, A CROSS SECTIONAL STUDY - Kunihira, Joyce Florence; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2025)
Background Ora- Quick HIV self-testing (HIVST) is where a person collects his or her specimen (oral fluid), performs an HIV test, and interprets the result either alone or with someone he or she trusts. The study was to assess Knowledge, Attitude, and Practices towards the utilization of Ora-Quick HIVST among pregnant mothers attending ANC at ERRH. Methodology A quantitative descriptive cross-sectional study design was used to select 40 mothers using a simple random sampling method, collecting data using a structured questionnaire. Data was analyzed using SPSS. Results Most 21) of the respondents (52.5%) were aged 18-24 years, while only 1(2.5%) was aged 35 and above. Half 20(50%) were Baganda tribe. The study indicated that 97.5% of respondents reported having heard of Ora-Quick HIV ST. 51.3% heard it from friends and family. 67% did not know that Ora-Quick is available in pharmacies. All the respondents knew that Ora-Quick HIVST is an acceptable idea, 40% disagreed that HIVST has the potential to reach hard-to-reach areas and 28% said they would not seek help and follow up an HIV positive result on Ora-Quick, 62.5% of the participants had never used an Ora-Quick HIVST, 64% did not know the correct time to read the results and 50% considered positive results to be the final. Conclusion Therefore, the study revealed insufficient knowledge as well as poor attitudes and practices towards Ora-Quick HIVST, which is believed to be related to inadequate community sensitization. The government, through the Ministry of Health, should launch national campaigns to promote HIV self-testing among pregnant mothers, emphasizing its role in early detection and prevention of mother-to-child transmission. Recommendation The government, through the Ministry of Health, should launch national campaigns to promote HIV self-testing among pregnant mothers, emphasizing its role in early detection and prevention of mother-to-child transmission.